Effects of strain/stress on quantum dots and nano-devices. - Shen, Zexiang. (2009)
Raman microscopy is a versatile characterization technique in research and industry. The main stumbling block of employing Raman microscopy in nanoscience and nanotechnology is the diffraction-limited spatial resolution. Several approaches have been employed to improve the spatial resolution to nanometer scale, among which laser delivered through metal-coated tapered optical fiber (aperture)1-3 and tip-enhanced (apertureless)4-6 near-field Raman techniques are the most frequently used. In this letter, we report a new method on near-field Raman imaging with spatial resolution of about 80 nm, by trapping and scanning a dielectric microsphere over the sample surface in water. We have used this technique to resolve 65 nm technology device sample with poly-Si gates and SiGe stressors, as well as gold nanopatterns, and carbon nanotubes (CNTs) with excellent reproducibility.